Toxicity effects of sumithion on the breeding performance and viability of eggs, embryos and subsequent growth indices of Heteropneustes fossilis larvae (Journal of the Bangladesh Agricultural University, 2017)
Sumithion, an organophosphate pesticide, has been used extensively in agriculture as well as in broodfish and nursery ponds in Bangladesh. Although it is being applied for beneficial purposes but eventually it exhibits some short and long term toxic effects to the aquatic ecosystem. Therefore, the present study investigated the toxic effects of sumithion on the breeding performance and subsequent viability of embryos and larvae of Heteropneustes fossilis. A total of 400 adult H. fossilis were equally stocked in two ponds. Sumithion at the dose of 0.24 ppm was applied for four months every 7 days interval in one pond while the rest one was considered as control. No significant (p>0.05) difference was found in growth between the treated and control H. fossilis; however, fertilization and hatching rates of the eggs obtained from the treated group were significantly (p>0.05) lower than that of control. Subsequently, the embryos and larvae produced from the broods of the control pond were exposed to 5 different concentrations of sumithion (0.5, 1.0, 2.0, 4.0, and 8.0 ppm) against a control (0 ppm). Each concentration was assessed in five replicates having 200 eggs. Data obtained from the sumithion acute toxicity tests were evaluated using the Probit Analysis. The mortality of embryos increased with the increasing sumithion concentrations from 0 to 8.0 ppm and the significant (p>0.05) differences were found only among the treated concentrations above 2.0 ppm. The 24 h LC50 value for embryos was estimated to be 7.803 ppm. Dose-response decreased in hatching success and recorded as 90.8, 85.0, 76.2, 73.0, 65.0, and 51.2 % for control and 5 different concentrations of sumithion, respectively (p